2014
DOI: 10.3389/fphys.2014.00213
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vitamin D in breast cancer: genomics, pathways, metabolism

Abstract: Nuclear receptors exert profound effects on mammary gland physiology and have complex roles in the etiology of breast cancer. In addition to receptors for classic steroid hormones such as estrogen and progesterone, the nuclear vitamin D receptor (VDR) interacts with its ligand 1α,25(OH)2D3 to modulate the normal mammary epithelial cell genome and subsequent phenotype. Observational studies suggest that vitamin D deficiency is common in breast cancer patients and that low vitamin D status enhances the risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 99 publications
(129 reference statements)
8
75
0
Order By: Relevance
“…Also in colorectal cancer, increased CYP24A1 gene copy number is shown, whereas no differences in CYP24A1 promoter methylation are seen (189). In agreement with these findings, 10 -13% of human breast cancers in the dataset from The Cancer Genome Atlas show altered CYP24A1 expression, most often due to gene amplification and characterized by enhanced mRNA levels (323). Of note, high CYP24A1 expression significantly correlates with poor survival in lung cancer cohorts (50).…”
Section: Vdr Expression and Vitamin D Metabolism In Cancer Cellssupporting
confidence: 73%
See 3 more Smart Citations
“…Also in colorectal cancer, increased CYP24A1 gene copy number is shown, whereas no differences in CYP24A1 promoter methylation are seen (189). In agreement with these findings, 10 -13% of human breast cancers in the dataset from The Cancer Genome Atlas show altered CYP24A1 expression, most often due to gene amplification and characterized by enhanced mRNA levels (323). Of note, high CYP24A1 expression significantly correlates with poor survival in lung cancer cohorts (50).…”
Section: Vdr Expression and Vitamin D Metabolism In Cancer Cellssupporting
confidence: 73%
“…Recently, Narvaez et al (323) reported that in The Cancer Genome Atlas datasets Ͻ2% of breast cancers exhibit genomic alterations (including amplifications, deletions, mutations, and changes in mRNA) (323). Nonetheless, multiple studies reported that in human cancer biopsies CYP27B1 mRNA expression (32, 47) and CYP27B1 protein levels (93,272,299) tend to be higher in well-differentiated tumors, whereas they are lower in more malignant and poorly differentiated tumors.…”
Section: Vdr Expression and Vitamin D Metabolism In Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular-based epidemiological studies have identified several functional polymorphisms in the VDR [21] and have demonstrated that the variants can affect the function of the receptor by altering its affinity to vitamin D [28,29]. VDR genetic variants have previously been associated with a number of diseases including pulmonary tuberculosis, diabetes, osteoporosis, asthma, ulcerative colitis, breast and female reproductive cancers, melanoma, systemic lupus erythematous and rheumatoid arthritis, Parkinson's disease, and coronary artery disease [30][31][32][33][34][35][36][37][38][39]. Pharmacogenetic studies have shown that VDR polymorphisms can modulate the response to a number of drugs including anti-tubercular and anti-psoriatic medications, anti-osteoporotic agents in postmenopausal women, interferon and ribavirin in patients with hepatitis C, vitamin D supplementation, and calcitriol [40][41][42][43][44][45][46], as well as with statin-induced myopathy [47].…”
Section: Discussionmentioning
confidence: 99%